Lack of IRF6 Disrupts Human Epithelial Homeostasis by Altering Colony Morphology, Migration Pattern, and Differentiation Potential of Keratinocytes - Girousi, Eleftheria; Muerner, Lukas; Parisi, Ludovica; Rihs, Silvia; von Gunten, Stephan; Katsaros, Christos; Degen, Martin (Frontiers in Cell and Developmental Biology, 2021)
Variants within the gene encoding for the transcription factor Interferon Regulatory Factor 6 (IRF6) are associated with syndromic and non-syndromic Cleft Lip/Palate (CLP) cases. IRF6 plays a vital role in the regulation of the proliferation/differentiation balance in keratinocytes and is involved in wound healing and migration. Since a fraction of CLP patients undergoing corrective cleft surgery experience wound healing complications, IRF6 represents an interesting candidate gene linking the two processes. However, Irf6 function has been mainly studied in mice and knowledge on IRF6 in human cells remains sparse. Here, we aimed to elucidate the role of IRF6 in human postnatal skin- and oral mucosa-derived keratinocytes. To do so, we applied CRISPR/Cas9 to ablate IRF6 in two TERT-immortalized keratinocyte cultures, which we used as model cell lines. We show that IRF6 controls the appearance of single cells and colonies, with the latter being less cohesive in its absence. Consequently, IRF6 knockout keratinocytes often moved as single cells instead of a collective epithelial sheet migration but maintained their epithelial character. Lack of IRF6 triggered severe keratinocyte differentiation defects, which were already apparent in the stratum spinosum and extended to the stratum corneum in 3D organotypic skin cultures, while it did not alter their growth rate. Finally, proteomics revealed that most of the differentially expressed proteins in the absence of IRF6 could be associated with differentiation, cell-cell adhesion as well as immune response. Our data expands the knowledge on IRF6 in human postnatal keratinocytes, which will help to better understand IRF6-related pathologies.